Robotic-assisted colorectal surgery in colorectal cancer management: a narrative review of clinical efficacy and multidisciplinary integration - Chen, Engeng; Chen, Li; Zhang, Wei (Frontiers in Oncology, 2025)
Colorectal cancer (CRC) remains a formidable global health challenge, ranking among the most prevalent malignancies and a principal contributor to cancer-associated mortality. While traditional open surgery has historically been the cornerstone of CRC treatment, the advent of minimally invasive techniques, particularly robotic-assisted colorectal surgery (RACS), has garnered significant momentum owing to technological advancements in the field. Robotic platforms, exemplified by the da Vinci Surgical System, offer superior three-dimensional visualization, enhanced dexterity, and heightened precision, yielding improved perioperative outcomes, particularly in anatomically intricate regions such as the pelvis. This review provides a critical appraisal of the current landscape of RACS, emphasizing its superiority over conventional open and laparoscopic approaches. The increased control and precision afforded by robotic surgery have been shown to optimize outcomes in complex procedures such as total mesorectal excision, with evidence indicating reduced intraoperative blood loss, shortened hospital stays, and improved functional recovery. Nonetheless, challenges persist, including absence of haptic feedback, prohibitive costs, and steep learning curve associated with robotic systems. Despite these limitations, RACS has demonstrated considerable promise in sphincter-preserving and function-preserving procedures, ultimately enhancing postoperative quality of life. Beyond the surgical field, this review also investigates the integration of robotic surgery within multidisciplinary treatment strategies for CRC, particularly in the context of locally advanced rectal cancer. The combination of robotic techniques with total neoadjuvant therapy and immunotherapy—especially in tumors characterized by mismatch repair deficiency or high microsatellite instability has shown notable clinical efficacy. Furthermore, emerging personalized therapeutic approaches, including immunotherapies and targeted chemotherapeutic agents, emphasize the transformative potential of RACS in delivering superior oncologic outcomes. Looking towards the future, innovations in robotic platforms, including intraoperative imaging, artificial intelligence, and augmented reality, herald new possibilities for further enhancing the precision and efficacy of colorectal surgeries. The standardization of RACS protocols, alongside ongoing training and robust clinical research, will be critical to fully realizing the benefits of these advancements across diverse clinical settings. By incorporating cutting-edge technologies and personalized treatment methods, robotic-assisted surgery is prepared to become a cornerstone in future of CRC management, with the potential to significantly improve both survival outcomes and patient quality of life.